Genome-Wide Analysis of KNOX Transcription Factors and Expression Pattern of Dwarf-Related KNOX Genes in Pear - Liu, Jianlong; Zhang, Chenxiao; Han, Jingyue; Fang, Xiaoyun; Xu, Hongpeng; Liang, Chenglin; Li, Dingli; Yang, Yingjie; Cui, Zhenhua; Wang, Ran; Song, Jiankun (Frontiers in Plant Science, 2022)
KNOTTED1-like homeobox (KNOX) transcription factors (TFs) belonging to the homeobox TF family play important roles in plant growth, development, and responses to abiotic and biotic stress. However, little information is available on KNOX TF in pear (Pyrus). In this study, 19 PbKNOXs TFs were re-identified in pear (Pyrus bretschneideri Rehd.). Phylogenetic analysis revealed that the TFs were clustered into three groups with 10 conserved motifs, some of which were group- or subgroup-specific, implying that they are important for the functions of the KNOX in these clades. PbKNM1 and PbKNM2 are KNM (encodes a MEINOX domain but not a homeodomain) genes identified in pear for the first time. KNOX genes in Pyrus and Malus were closely related, and a collinear relationship among PbKNOX genes in Pyrus and Malus was observed. Analysis of the expression patterns of PbKNOX genes in different tissues, at various growth stages, and in response to abiotic and biotic stress revealed that PbKNOXs are involved in plant growth and development. Our comparative transcriptional analysis of dwarf mutant varieties revealed that genes belonging to class I are highly expressed compared with genes in other classes. Analysis of the expression of PbKNOX genes in the hybrid offspring of vigorous and dwarf varieties revealed that PbKNOX genes were highly expressed in the vigorous offspring and weakly expressed in the dwarf offspring. These findings provide new insight into the function of KNOX TFs in pear and will aid future studies of dwarf fruit trees.